Immunopathological features of highly pathogenic Korean Lineage B PRRSV-2: insights into virulence indicators and host immune responses - Gyeong-Seo Park; Gyeong-Seo Park; Seung-Chai Kim; Hwan-Ju Kim; Chang-Gi Jeong; Chang-Gi Jeong; Sang-Chul Kang; Go-Eun Shin; Seoung-Hee Kim; Hye-Young Jeong; Kyoung-Ki Lee; Sang-Myeong Lee; et al. (Frontiers in Immunology)
IntroductionPorcine reproductive and respiratory syndrome virus (PRRSV) remains one of the most economically devastating pathogens in swine, primarily due to its extensive genetic diversity and lineage-dependent pathogenicity. Despite widespread vaccination, distinct PRRSV-2 lineages continue to circulate in Korea. This study aimed to elucidate the immunopathological features of two Korean-specific Lineage B (LKB) strains, GGYC45 and PJ10, compared with a vaccine-like L5 strain, M8.MethodsThirty, 4-week-old piglets were divided into M8-, GGYC45-, PJ10-infected groups, and control. After acclimatization, pigs were intramuscularly inoculated with PRRSV-2 strains. Pigs were monitored, and blood and nasal swabs were collected. At 12- and 28 days post-infection (dpi), pigs were euthanized for histopathological analysis and tissue collection. Histopathological evaluations were conducted on lung and brain tissues. Bronchoalveolar lavage (BAL) cells and lung tissues were analyzed for immune responses, including flow cytometry (FACS), cytokine expression, viral load, and expression of immune checkpoint molecules.ResultsBoth LKB strains (GGYC45 and PJ10) observed moderate to severe clinical symptoms. Notably, PJ10-infected pigs exhibited high mortality accompanied by significantly (p < 0.05) low average daily weight gain (ADWG), high temperatures, and high levels of viremia and viral loads in various tissues. Immunopathological analysis showed severe respiratory and neurological lesions in PJ10-infected pigs. PJ10 destroyed over 90% of residential alveolar macrophages and increased infiltrated monocyte-derived cells and T lymphocytes in the lungs up to 12 dpi. Pigs infected with the GGYC45 strain exhibited a relatively lower virulence profile than those infected with the PJ10 strain; however, GGYC45 induced moderate pathogenicity in pigs. Regardless of the lineages or genotypes, pigs infected with PRRSV-2 increased immune checkpoint molecule expression, such as PD1, PDL1, CTLA4, IDO1, and LAG3 in BAL cells, resulting in insufficient T cell activation.ConclusionThese results highlight the differential virulence and immunomodulatory profiles of genetically distinct PRRSV-2 strains circulating in Korea. The heightened immune checkpoint expression, particularly in PJ10-infected pigs, underscores a potential mechanism of PRRSV-induced immune suppression and viral persistence. This study provides critical insights into PRRSV pathogenesis and host-virus interactions and supports the need for lineage-adapted control strategies that account for both the genetic heterogeneity of PRRSV and immune evasion mechanisms.